Implementasi Algoritma Fuzzy logic Pada Tempat Sampah Pintar Menggunakan Sensor Ultrasonik Berbasis Arduino Uno - Herlambang, Ian; Hardianto; Saputra, Rizal Adi (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
Environmental issues are still one of the problems that need special attention. Among the problems regarding the environment, waste is one of the problems that is difficult to overcome. This is due to the high consumptive behavior of the community that produces a lot of waste or garbage. Smart trash cans use proximity sensors to make the trash can lid open automatically. To increase accuracy and simplify settings on smart trash can automation, in this research the author uses the Fuzzy logic algorithm. Smart trash cans are made with ultraviolet sensors based on Arduino Uno which are embedded with fuzzy algorithms so that the sensors can have better accuracy, easier settings, and are more resistant to interference. Based on the test results, the automatic trash can system using ultrasonic sensors can work well in various environmental conditions. The ultrasonic sensor used in this research has an accuracy of 95%. This means that the ultrasonic sensor can detect the presence of humans when trying to take out the trash with a high level of accuracy.